Hubungan Kompensasi terhadap Kinerja Karyawan Tenaga Kerja Kontrak di Rumah Sakit Bhayangkara Pekanbaru Tahun 2019 - Jihan Natassa Jihan; Ahmad Satria Efendi; Feby Ihsan Ayu (Jurnal Kesehatan Komunitas, 2020)
The importance of compensation for employees, a major influence on behavior and performance at Bhayangkara Hospital. The performance of Bhayangkara Hospital employees are low spotted with the works that is not finished on me, less hosle tovisitors and employees were less fast and skillful in serve up the patients.There is no procurement (reward) for employees who has committed with an excellent works. Especially for temporary employees with working hours and the workloads for that does not justify especially employees contract workers who worked on section room approximately 150 to 200 patients per day. The purpose of this research is to know the relationship betweensalary, incenves, award, and benefit for temporary employee’s performance at Bhayangkara Hospital Pekanbaru. Design study of this research was cross sectional.Populations for this study are all of temporary employees at Bhayangkara Hospital Pekanbaru with 121 samples (total sampling). Data analysis is used univariat and bivariat analysis by chi-square test. The results of the study of eight variable found 4 variable related significant with theperformance, namely salary, incenve, award, allowance, expected for hospitals give, the provision of incentives for employees TKK , the award for employees with the performanceof the best , and benefits that give in accordance with a role at the hospital and the workloads given . Keywords            : Salary, Incentives, Awards, Allowences